Telecommunication techniques and systems (III) - Lu, Chao. (2008)
In this report, based on the study of various gain-flattening and gain-control techniques, the investigators have proposed and demonstrated a new configuration of gain-equalized EDFA for WDM systems by using short-period fiber Bragg gratings (FBGs). It is named as multichannel gain-equalized amplifier (MGEA) in this report.